Implicitation and Deletion in the Translation of Band of Brothers Subtitle and Their Effect on the Translation Quality - Muhammad Fajar Aryana; M.R. Nababan; Djatmika Djatmika (Journal of Language and Literature, 2018)
The space for the subtitle has been a limited space for translators to accommodate the whole message from source to target language. However, the combination between textual multimodality and the techniques of how to make it more implicit should bridge the gap between message of the target text and the viewers. The viewers can still catch the meaning of the utterance not only based on the text but also from the other modality such as gesture, audio and other audio-visual effect on the scene.This study aims to find out the effect of implicitation and deletion, used in translating subtitle, on translation quality. The translation quality assessment includes the level accuracy, acceptability and readability of the text. This study is also a pilot study for the master degree thesis exploring the translation techniques, in this case implicitation and deletion, which are commonly used in subtitle to make the source text more implicit in the target text. Based on the findings of the research, the translators tends to apply implicitation rather than deletion to make the text more implicit.Keywords: implicitation, deletion, translation quality assessment